2020
DOI: 10.1371/journal.pmed.1003221
|View full text |Cite
|
Sign up to set email alerts
|

Predicting obesity reduction after implementing warning labels in Mexico: A modeling study

Abstract: Background In October 2019, Mexico approved a law to establish that nonalcoholic beverages and packaged foods that exceed a threshold for added calories, sugars, fats, trans fat, or sodium should have an "excess of" warning label. We aimed to estimate the expected reduction in the obesity prevalence and obesity costs in Mexico by introducing warning labels, over 5 years, among adults under 60 years of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 26 publications
0
50
0
4
Order By: Relevance
“…In a time when some countries, states, and cities are implementing mandatory nutrition policies, including taxes on soft drinks [ 11 ] and front-of-package warning labels [ 12 , 13 ], there is much interest and debate around whether voluntary initiatives are effective. The success of PHE’s voluntary sugar reduction policy is heavily dependent on action by the entire food industry to reduce the sugar content of its products and to encourage changes in consumer behaviour towards purchasing lower sugar alternatives by launching new product lines or focussing marketing and advertising practices on lower sugar products.…”
Section: Introductionmentioning
confidence: 99%
“…In a time when some countries, states, and cities are implementing mandatory nutrition policies, including taxes on soft drinks [ 11 ] and front-of-package warning labels [ 12 , 13 ], there is much interest and debate around whether voluntary initiatives are effective. The success of PHE’s voluntary sugar reduction policy is heavily dependent on action by the entire food industry to reduce the sugar content of its products and to encourage changes in consumer behaviour towards purchasing lower sugar alternatives by launching new product lines or focussing marketing and advertising practices on lower sugar products.…”
Section: Introductionmentioning
confidence: 99%
“…First, the expected change in NEDF intake due to the tax was obtained from an observational study that estimated the impact of the tax in NEDF purchases (15); thus, we had to assume that the observed changes in household purchases translate into changes in individual-level intake. This assumption is common to prior studies that have estimated the impact of sugarsweetened beverages on body weight (52)(53)(54)(55). We used the 5.1% decrease in NEDF household purchases reported by Batis et al as a conservative estimate, although a subsequent evaluation observed a mean reduction in NEDF purchases of 6.0% in 2014-2015, which is related to a larger reduction in purchases in the second year of tax (27).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, CHD excess mortality was mainly explained through increases in risk factors, mostly changes in diabetes, cholesterol and physical inactivity. These changes occurred along with rapid urbanization and changes in dietary patterns, leading to more physical inactivity and a transition from traditional to Westernised ultra-processed diet [41][42][43][44][45]. These changes in behavioral lifestyles have been associated with an increase in diabetes, obesity and hypercholesterolemia [16,23,45,46].…”
Section: Discussionmentioning
confidence: 99%
“…The fact that these risk factors share the same fundamental causes, points at the opportunities to implement population-based interventions to provide healthier contexts for diet and physical activity [ 22 ]. Over the past decade, Mexico has developed a clear agenda to reduce obesity and metabolic diseases, based on population interventions, such as taxes to unhealthy foods and food warning labels [ 41 , 42 ]. However, further population-based policies efforts will be needed to reduce obesity, diabetes and CHD deaths in Mexico.…”
Section: Discussionmentioning
confidence: 99%